2013
DOI: 10.1038/ng.2686
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association meta-analysis of self-reported allergy identifies shared and allergy-specific susceptibility loci

Abstract: Allergic disease is very common and carries substantial public-health burdens. We conducted a meta-analysis of genome-wide associations with self-reported cat, dust-mite and pollen allergies in 53,862 individuals. We used generalized estimating equations to model shared and allergy-specific genetic effects. We identified 16 shared susceptibility loci with association P<5×10(-8), including 8 loci previously associated with asthma, as well as 4p14 near TLR1, TLR6 and TLR10 (rs2101521, P=5.3×10(-21)); 6p21.33 nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
244
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(255 citation statements)
references
References 72 publications
9
244
0
2
Order By: Relevance
“…This gene previously met genome-wide association criteria in studies of sex hormone-binding globulin levels (linked to sex steroid regulation) (30) and asthma with hay fever (31). It has also shown suggestive levels of association in hypothyroidism (32), atopic dermatitis (33) and self-reported allergy (34). ZBTB10 is thought to regulate specificity proteins Sp1, Sp3 and Sp4 (35,36); in cell culture studies, it is suppressed by ROSmicroRNA27a, thereby enhancing estrogen receptor α expression and mediating estrogen effects (36).…”
Section: Discussionmentioning
confidence: 99%
“…This gene previously met genome-wide association criteria in studies of sex hormone-binding globulin levels (linked to sex steroid regulation) (30) and asthma with hay fever (31). It has also shown suggestive levels of association in hypothyroidism (32), atopic dermatitis (33) and self-reported allergy (34). ZBTB10 is thought to regulate specificity proteins Sp1, Sp3 and Sp4 (35,36); in cell culture studies, it is suppressed by ROSmicroRNA27a, thereby enhancing estrogen receptor α expression and mediating estrogen effects (36).…”
Section: Discussionmentioning
confidence: 99%
“…34 Consistently, recent genome-wide association studies (GWAS) identified the Ptger4 locus, the human EP4 gene, as one of the disease susceptibility loci in immune diseases, including Crohn's disease, 35 multiple sclerosis, 36 and allergies. 37 Furthermore, a recent study revealed that candidate causal single nucleotide polymorphism related to multiple sclerosis, Crohn's disease, allergies, and ulcerative colitis are enriched with acetylated H3K27-labled active enhancer regions at the Ptger4 locus and are well matched with expression of this gene as evidenced by the RNA sequence. 38 Introduction of therapeutic antibodies such as secukinumab, ustekinumab, and tildrakizumab to IL-17 and the two chains of IL-23 have greatly improved therapeutic outcomes for patients suffering from IL-23-IL-17 axis-driven immune diseases such as psoriasis, 6 rheumatoid arthritis, 7 ankylosing spondylitis, 8 and Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…This work showed that neonatal immune cells did indeed harbor 589 DMRs that distinguished IIS children who did and did not develop asthma by age 9. Network analysis revealed that these childhood asthma-associated DNA methylation signatures clustered in immunoregulatory and pro-inflammatory pathways; the transcription factor SMAD3, an asthma gene highly replicated in GWAS [18][19][20], was the most connected node within the network of asthma-associated DMRs. Of note, SMAD3 methylation was selectively increased in asthmatic children of asthmatic mothers and was associated with childhood asthma risk not only in IIS but also in two other comparable birth cohorts, the Manchester Asthma and Allergy Study (MAAS) and the Childhood Origins of ASThma (COAST) Study.…”
Section: The Epigenetic Trajectory To Asthma Begins At Birth (If Not mentioning
confidence: 99%